Space Syntax with Prolog - Fernandes, Pedro Afonso (2022)
This paper introduces a new way to perform space syntax analyses using Prolog, a Logic Programming language concerned with Artificial Intelligence. Developed in the 1970’s to process natural languages, Prolog can deal easily with simple declarations of facts like the connection (or permeability) between convex spaces or axial lines. Readily available on-line through the SWISH platform, in a fancy format inspired by Jupyter Notebooks, Prolog may help to understand the recursive nature of urban processes, given some elementary generators, or to describe or even check the structure (e.g. concentric) of some village. Mostly important, Prolog can compute space syntax measures such connectivity, control or integration in a comprehensive, transparent and attractive way, namely, for students and researchers on space syntax. The experience suggests that Prolog may be appropriate for gamma-analysis of small buildings like the Ashanti’s shrine, acting as flexible and easily replicable calculator of syntactic measures. This flexibility is reinforced by the free and open-source nature of the code stored in the SWISH platform, as well as by the declarative nature of Logic Programming, which facilitates the description of the patterns of discrete systems as social knowables. In fact, a Prolog program represents a certain amount of knowledge, which is used to answer queries about the social and economic consequences of some spatial design.